Penguatan Literasi Keuangan Berbasis Digital untuk Peningkatan Ekonomi pada Pelaku Usaha Produk Kopra Desa Lapeo Kabupaten Polewali Mandar - Wulan Ayuandiani; Nur Ariyandani; Dian Rahmayanti Rivai (PaKMas: Jurnal Pengabdian Kepada Masyarakat, 2025)
Polewali Mandar is an area that has diverse natural resource potential derived from agriculture and plantations. One of the abundant natural resources is the largest producer of coconuts in West Sulawesi. This potential is an important part of generating income for the community in the region. One of the commodities with the highest plantation production is coconut, both copra and hybrid coconut. There are 17,498 tons of coconut plantation products in the Polewali Mandar area, making it the highest plantation commodity compared to other districts in West Sulawesi Province. Some of the problems faced are as follows: the first problem is that copra farmers only understand and use simple financial recording. The second problem is the low understanding of using digital-based financial applications. The solutions offered in the community service activities are: 1) The service providers will provide socialization to the Lapeo Village Copra Product Business Actors group about the opportunities to increase income through understanding digital-based finance, and 2) The service providers will offer solutions to conduct training on the use of digital-based financial applications (financial technology). The proposed activity plan includes: 1) Preparation stage, 2) Socialization regarding Understanding Digital-Based Financial Literacy in Lapeo Village, 3) Training on the use of Digital-Based Financial Applications (Financial Technology) with an approach to training and strengthening for collaboration between MSME actors and local government to develop and increase the income of business actors, 4) Evaluation. The target output to be achieved is publication in a National Scientific Journal.